Protease-resistant streptavidin for interaction proteomics - Rafiee, Mahmoud-Reza; Sigismondo, Gianluca; Kalxdorf, Mathias; Förster, Laura-Christin; Brügger, Britta; Béthune, Julien; Krijgsveld, Jeroen (Molecular systems biology, 2020)
Abstract Streptavidin-mediated enrichment is a powerful strategy to identify biotinylated biomolecules and their interaction partners; however, intense streptavidin-derived peptides impede protein identification by mass spectrometry. Here, we present an approach to chemically modify streptavidin, thus rendering it resistant to proteolysis by trypsin and LysC. This modification results in over 100-fold reduction of streptavidin contamination and in better coverage of proteins interacting with various biotinylated bait molecules (DNA, protein, and lipid) in an overall simplified workflow.
Gesehen am 17.8.2020